Whole-body energy transfer strategies during football instep kicking: implications for training practices - Augustus, S.; Hudson, P. E.; Harvey, N.; Smith, N. (Sports Biomechanics, 2024)
Knowledge of whole-body energy transfer strategies during football instep kicking can help inform empirically grounded training practices. The aim of this study was thus to investigate energy transfer strategies of 15 semi-professional players performing kicks for speed and accuracy. Three-dimensional kinematics and GRFs (both 1000Hz) were incorporated into segment power analyses to derive energy transfers between the support leg, torso, pelvis and kick leg throughout the kick. Energy transferred from support leg (r=0.62, P =0.013) and torso (r=0.54, P =0.016) into the pelvis during tension arc formation and leg cocking was redistributed to the kick leg during the downswing (r=0.76, P <0.001) and were associated with faster foot velocities at ball contact. This highlights whole-body function during instep kicking. Of particular importance were: (a) regulating support leg energy absorption, (b) eccentric formation and concentric release of a 'tension arc' between the torso and kicking hip, and (c) coordinated proximal to distal sequencing of the kick leg. Resistance exercises that replicate the demands of these interactions may help develop more powerful kicking motions and varying task and/or environmental constraints might facilitate development of adaptable energy transfer strategies.